Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Pada E-Commerce Shopee di Kota Batam - Nissia Amanda Br Purba; Suhardi Suhardi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study was conducted to examine the influence of product quality and brand image on consumer purchasing decisions on the Shopee e-commerce platform in Batam City using a descriptive quantitative approach that emphasizes measuring cause-and-effect relationships between variables objectively and in a structured manner. The research respondents were 204 people who were active Shopee users and had experience purchasing products through the platform, with the sample determination using a purposive sampling technique and considering the Jacob Cohen approach to ensure the adequacy of the sample size. The research data were analyzed through a series of testing stages, including instrument validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing to determine the contribution of each independent variable. The results of the analysis showed that product quality contributed 43.7% to purchasing decisions, while brand image had an influence of 24.2%, and simultaneously the two variables were able to explain 74.6% of the variation in consumer purchasing decisions based on the coefficient of determination (R²), while the rest was influenced by other factors outside the research model, so it can be concluded that product quality and brand image partially or together have a significant influence on purchasing decisions on Shopee e-commerce in Batam City.